ANALISIS PERILAKU PEMBELIAN IMPULSIF PRODUK FASHION DILIHAT DARI PERBEDAAN USIA - Lily Suhaily; Yasintha Soelasih (Bina Ekonomi, 2014)
The purpose of this research is to analyse impulsive buying behavior of fashion product based on age differences. 260 questionnaires were distributed to respondents at Plaza Semanggi, Sudirman with random sampling method. The resut shows that no differences between young adults and maturity adults age toward impulsive buying behavior of fashion product.